2014
DOI: 10.1002/2013jc009197
|View full text |Cite
|
Sign up to set email alerts
|

Determination of particulate organic carbon sources to the surface mixed layer of the Canada Basin, Arctic Ocean

Abstract: Stable isotope ratios of particulate organic carbon (POC), together with other tracers, were ana- generally found in the central basin. Isotopically enriched material was found on the shelves, consistent with higher biological production and strongly correlated with in situ carbon-uptake rates. In contrast, offshore in the central basin, there was no significant relationship between d 13 C-POC distributions and either chlorophyll a or aqueous CO 2 concentrations, suggesting that in situ biological production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 70 publications
(137 reference statements)
8
14
0
Order By: Relevance
“…The presence of brine waters was congruent with higher salinity (25.61−29.34; Figure ) and ice cover (>95%; Figure ) in July−August 2011. Brown et al () found negative f SIM and high salinity in the northwest mixed layer Canada Basin in July−August 2008, indicating convective mixing due to sea ice formation. The higher sea ice cover in 2011 (Figure ) may have also resulted in a lower exposure of DOM to solar radiation in surface waters and limited photobleaching of humic‐like (C1‐C2 and C4) previously identified as photolabile FDOM components (Dainard et al, ; Logvinova et al, ; Stedmon et al, ; Stedmon & Markager, ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of brine waters was congruent with higher salinity (25.61−29.34; Figure ) and ice cover (>95%; Figure ) in July−August 2011. Brown et al () found negative f SIM and high salinity in the northwest mixed layer Canada Basin in July−August 2008, indicating convective mixing due to sea ice formation. The higher sea ice cover in 2011 (Figure ) may have also resulted in a lower exposure of DOM to solar radiation in surface waters and limited photobleaching of humic‐like (C1‐C2 and C4) previously identified as photolabile FDOM components (Dainard et al, ; Logvinova et al, ; Stedmon et al, ; Stedmon & Markager, ).…”
Section: Discussionmentioning
confidence: 99%
“…[, and references therein]. Results of suspended POC collected in the surface mixed layer of the Canada Basin in 2008 and 2009 [ Brown et al ., ] are also shown.…”
Section: Discussionmentioning
confidence: 99%
“…2F, 2H) have low salinities resulting from addition of sea-ice meltwater, or Mackenzie River runoff (Brown et al, 2014). These samples do not plot with the conservatively mixing Pacific and Atlantic waters in Figs.…”
Section: Beaufort Seamentioning
confidence: 92%
“…2F, 2H; Table 2). The δ 53 Cr of these samples (+1.47 to +1.53h) are among the highest in the Arctic data set, and have the lowest [Cr] (64-74 ng/kg), as well as low salinity (25.3-25.7), which reflects a larger proportion of water from the Mackenzie River and sea ice melt (Brown et al, 2014). Also at L1.1 (50 m), a sample from the remnant of the winter mixed layer (Jackson et al, 2012) was analyzed in duplicate (Fig.…”
Section: Chromium Isotopes In Seawatermentioning
confidence: 99%